An ECOLOGICAL FUNCTIONALISME ARCHITECTURE KARYA GLENN MURCUTT - Harmilyanti Sulistyani (Pendhapa, 2012)
Architecture as a cultural product is used to develop human welfare. Knowledge about the environment and climate are the uniqueness of Glenn Murcutt design. The choices of technology, material and the form show that he consistent to keep alive the natural resource. Modern material and technology selected to support his effort to optimizing the environment use in design.Deductive method is used to explore Ecological functionalism principal. Essay and article that contain about Glenn Murcutt vision and design are taken as a data source. The data indentified to catch the design concept. Graphic analyze are used to find the application in design, by this way ecological functionalism concept in Glenn Murcutt design will be found.Glenn Murcutt is applicative ecological functionalism concept in his design. He used special material with modern technology to optimize the environment potential. Topography and the climate characteristic is the base of design. Simple and aerodynamic forms are choosing as activity facility. The selected material and form do not just a part of structure but also a piece of the aesthetic. Key words: climate caracteristic, simple kurva, aerodynamic, modern technology.